대형 융합 연구사업의 최선단 연구기획 관리전략 - 송용일; 이대희; 박성배; 정윤철 (기술경영경제학회, 2004)
As the speed of technological changes increase with the investment requirements steadily expanding, private firms and government-funded research institutes experience similar pressures with respect to the necessity of risk reduction and technological alliances in R&D activities. This paper first attempts to review previous research in managing R&D projects with large, risky, and long-term investment requirements. Our primary focus is placed on the "fuzzy front-end" (FFE) projects with uncertainties at the investigation and planning stages. We analyze various elements that create FFE conditions, classify them into basic constructs, and suggest tools and methods to deal with FFE conditions. The findings suggest that both initial FFE conditions and the effectiveness of FFE management affect the performance of the project later on, and thus, especially for large projects, we must deal with FFE seriously in a comprehensive manner. We utilize in-depth panel interviews and case studies to approach the research questions.